CORTISOL-SECRETING ADRENOCORTICAL CARCINOMA IN A BLUE HEELER - Isabely Stelzer Tinelli; Luisa Frasson Vieira; Jéssica Miranda Cota; Orlando Chiarelli-Neto; Maria Emilia Pozzatti Souza; Haide Valeska Scheid; Rafael Mazioli Barcelos; Clairton Marcolongo Pereira (UNESC em Revista, 2025)
Adrenocortical tumors in dogs are uncommon, but clinically important neoplasms, especially when they are functionally active and associated with cortisol overproduction. These tumors can lead to classic signs of hypercortisolism including polyuria, polydipsia, polyphagia, muscle wasting, and abdominal distension. This report describes the clinical, imaging, and histopathological findings of cortisol-secreting adrenocortical carcinoma in a 14-year-old female Blue Heeler dog that presented with progressive abdominal distension, exophthalmos, and systemic hypertension. The initial diagnostic workup revealed hyperlipidemia and increased alkaline phosphatase levels. The low-dose dexamethasone suppression test failed to suppress the hypothalamic-pituitary-adrenal axis, indicating endogenous hypercortisolism. Contrast-enhanced computed tomography revealed a nodular mass in the left adrenal gland with internal calcification, renal vein displacement, and no vascular invasion. The dog underwent adrenalectomy, and histopathological analysis confirmed a diagnosis of adrenocortical carcinoma. The neoplasm displayed a solid and infiltrative pattern, capsular invasion, hemorrhage, and dystrophic calcification. The partial Utrecht histological scoring system yielded a score of 7, suggesting an intermediate malignancy and risk of recurrence. Liver biopsy revealed marked macro-and microvesicular hepatocellular vacuolar degeneration, predominantly in the centrilobular and midzonal areas, which was consistent with chronic glucocorticoid exposure. This case illustrates the importance of integrating clinical signs, hormonal testing, advanced imaging, and histopathological evaluation for the accurate diagnosis and management of functional adrenocortical tumors in dogs. It also emphasizes the relevance of histological scoring systems, such as the Utrecht Score, in predicting biological behavior and guiding therapeutic decisions in veterinary oncology. Keywords: Adrenal neoplasm. Cortisol-secreting tumor. Hypercortisolism. Adrenalectomy. Utrecht score.